Resolução CSMPF nº 145, de 5 de agosto de 2013 - Roberto Monteiro Gurgel Santos; Sandra Veronica Cureau; Helenita Amelia Caiado Goncalves de Acioli; Moacir Guimaraes Morais Filho; Maria Caetana Cintra Santos; Rodrigo Janot Monteiro de Barros; Raquel Elias Ferreira Dodge; Elizeta Maria de Paiva Ramos; Antonio Augusto Brandao de Aras (DMPF-e, Brasília, DF, 20 set. 2013. Caderno Extrajudicial, p. 3, 2013)
Dispõe sobre o Regimento Interno da 3ª Câmara de Coordenação e Revisão do Ministério Público Federal.